2023
DOI: 10.1002/ardp.202200470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the pKa value on the antioxidant activity of licorice flavonoids under solvent‐mediated effects

Abstract: Licorice flavonoids (LCFs) have been widely used in food care and medical treatment due to their significant antioxidant activities. However, the molecular mechanism of their antioxidant activity remains unclear. Therefore, network pharmacology, ADMET, density functional theory (DFT), molecular docking, and molecular dynamics (MD) simulation were employed to explore the molecular mechanism of the antioxidant effects of LCF. The network pharmacology and ADMET studies showed that the active molecules of kumatake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…GA is the aglycone of glycyrrhizic acid, and a study by Agarwal et al [39] demonstrated that glycyrrhizic acid was able to attenuate oxidative stress damage induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) in mouse skin. Licorice flavonoids also exhibit significant antioxidant activity [40,41] . Zeng et al [42] investigated the protective effect of licorice flavonoids against kainate (KA)-induced seizures in mice and found that treatment with licorice flavonoids after seizures reduced KA-induced SOD activity and malondialdehyde (MDA) content on the seventh as well as 28th day, indicating that licorice flavonoids have a protective effect against epilepsy-induced neuronal cell death and cognitive deficits, probably through their antioxidant effects.…”
Section: Anti-oxidant Activitymentioning
confidence: 99%
“…GA is the aglycone of glycyrrhizic acid, and a study by Agarwal et al [39] demonstrated that glycyrrhizic acid was able to attenuate oxidative stress damage induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) in mouse skin. Licorice flavonoids also exhibit significant antioxidant activity [40,41] . Zeng et al [42] investigated the protective effect of licorice flavonoids against kainate (KA)-induced seizures in mice and found that treatment with licorice flavonoids after seizures reduced KA-induced SOD activity and malondialdehyde (MDA) content on the seventh as well as 28th day, indicating that licorice flavonoids have a protective effect against epilepsy-induced neuronal cell death and cognitive deficits, probably through their antioxidant effects.…”
Section: Anti-oxidant Activitymentioning
confidence: 99%
“…Nevertheless, there are some studies showing the opposite. For example, Yi Hu et al found that for licorice flavonoids, a higher pK a value correlated with a higher solvent-mediated antioxidant activity [ 64 ]. Apparently, we have not yet found a clear-cut relationship between pK a and free radical scavenging ability, and this is the subject of ongoing research.…”
Section: Computational Chemistry Strategies To Investigate the Antiox...mentioning
confidence: 99%
“…RDF is a probability density distribution of finding another particle at a distance r in a system composed of atoms, molecules, or ions, which describes the density distribution of surrounding atoms or molecules at a distance r and can be used to describe the interaction between atoms, molecules, or ions in solids, liquids, or gases. [57][58][59] Generally, when the peak of g(r) is less than 3.5 Å, it indicates that hydrogen bonds are formed between molecules. 44 As shown in Fig.…”
Section: Rdf Analysismentioning
confidence: 99%
“…1a), a natural flavonoid extracted from the root of licorice, has a variety of biological activities. 26,27 Firstly, it can be used as a sweetener and is widely used to sweeten foods and drugs. 28 Secondly, it has anti-inflammatory, 29 antioxidant, 30 and other effects, and has been used to treat AIDS 31 and other diseases.…”
Section: Introductionmentioning
confidence: 99%